Rancang Bangun Alat Penghitung Benih Ikan Otomatis Berbasis Blynk IoT - Boby Wisely Ziliwu (Lembaga Dongan Dosen, 2025)
Cultivators can never run smoothly in their business, sometimes experiencing obstacles. One of the obstacles that is often encountered is the calculation of the number of fish seeds that are not correct/inappropriate due to the large number ordered up to hundreds or even thousands of seeds. In terms of counting fish seeds, fish cultivators have been serving fish buyers by doing the calculations manually, namely the fish are taken one by one from a container by hand, then transferred to the aquaculture pond. In calculating the seeds of this fish must be done accurately, efficiently, and quickly. Because in doing manual counting or moving fish one by one, if the fish take too long it can cause the fish seeds to become stressed because they cannot be separated from the age of the fish seeds which are relatively only a few weeks old. If the fish are stressed, of course it can cause the fish to die and can make fish cultivators lose a lot. Automatic Fish Counter tool system that can count koi fish seeds using the E18-DN80K sensor. This tool can be integrated via WiFi, namely using Blynk IOT. For the average occurrence of calculation errors when this system reads the number of fish seeds, which is 4%. It can be concluded that this tool can function properly to assist fish cultivators in calculating fish fingerlings when they have just bought fish seeds, or fish cultivators who want to sell their fish seeds by using an Android-based WiFi system application.